Analysis of the Influence of NPL and DER on ROA at PT Artha Graha International Bank Tbk - Sari, Indah Putri; Rimawan, M.; Muniarty, Puji (Jurnal Ilmu Manajemen Profitability, 2025)
This study aims to analyze the effect of Non-Performing Loans (NPL) and Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT. Bank Artha Graha Internasional, Tbk. The research employs an associative approach using quantitative data from the bank's financial statements over a ten-year period from 2013 to 2022. The dataset includes total non-performing loans, total credit, total debt, total equity, net profit, and total assets. The research population spans 32 years, while the sample consists of 10 years selected through a purposive sampling technique. The study utilizes secondary data collected through documentation and literature review. Data analysis includes classical assumption tests, multiple linear regression analysis, correlation coefficients, determination tests, t-tests, and F-tests, conducted using SPSS version 24. These statistical methods are applied to examine the relationship between NPL, DER, and ROA and to determine the significance of their impact. The findings indicate that NPL and DER do not have a significant effect on ROA, either partially or simultaneously, at PT. Bank Artha Graha Internasional, Tbk. Although the relationship between these variables is of moderate strength, it suggests that other financial or external factors may play a more influential role in determining the bank’s profitability. These results highlight the need for further research to explore additional determinants of financial performance in the banking sector, considering aspects such as operational efficiency, risk management, and macroeconomic conditions that may influence profitability.